Mortality Risk in Insects - Peterson, Robert K. D.; Davis, Ryan S.; Higley, Leon G.; Fernandes, Odair A. [UNESP] (Entomological Soc Amer, 2009)
Understanding how and why insect numbers fluctuate through time and space has been a central theme in ecological research for more than a century. Life tables have been used to understand temporal and spatial patterns in insect numbers. In this study, we estimated cause-of-death probabilities for phytophagous insects using multiple decrement life tables and the irreplaceable mortality analytic technique. Multiple decrement life tables were created from 73 insect life tables published from 1954 to 2004. Irreplaceable mortality (the portion of mortality that cannot be replaced by another cause) from pathogens, predators, and parasitoids was 8.6 +/- 7.2, 7.8 +/- 4.9, and 6.2 +/- 1.6%, respectively. In contrast, the mean irreplaceable mortality from all non-natural enemy mortality factors (mortality from factors other than natural enemies) was 35.1 +/- 4.4%. Irreplaceable mortality from natural enemies was significantly lower compared with non-natural enemy factors. Our results may partially explain cases of unsuccessful efficacy in classical biological control, after successful establishment, by showing low irreplaceable mortality for natural enemies, including 5.2 +/- 1.6% for introduced natural enemies. We suggest that the environment (i.e., the degree of environmental stability) influences the magnitude of the irreplaceable mortality from natural enemies. Our results lead to several testable hypotheses and emphasize that it is not possible to estimate the effect of any mortality factor without considering its interaction with competing mortality factors, which has far-reaching consequences for population biology and applied ecology.
Keywords: risk analysis; multiple decrement life table; Biological control; Natural enemies; insect demography